Caregivers of Mentally Ill Patients: A Cross-sectional Need-Based Assessment of Social Workers in Post-conflict Somalia. Issue 1 (1st January 2020) - Arkorful, Vincent Ekow; Mohamed, Adam A.; Jama, Osman; Pokuaah, Sarah; Basiru, Ibrahim; Hammond, Anastasia; Agyei, Eric Kwadwo; Latif, Amadu
Abstract : This study seeks to investigate the needs of family caregivers of people living with Mental illness in Somalia. Using an exploratory research design technique, a qualitative approach was employed for a one-on-one interview module to collect data from a total of 51 respondents identified as family caregivers of mentally ill persons undergoing rehabilitation in five (5) selected mental health facilities sampled for the study. In analyzing and interpreting qualitative data, a thematic content analysis was done which revealed that, in addition to medical care, family caregivers need not only social support in a form of affection to assist them in their various engagements, but also, adequate relaxation and leisure to regain lost energies and save them from stress and its harmful ramifications on their health. They also need decent accommodation to maintain their mentally ill relatives. The results further revealed that, caregivers needed financial support as well as emotional support from friends and society in order to psyche them up for their task. To understand the needs of patients' treatment history and condition, caregivers need information. It is, therefore of necessity to social workers and other stakeholders that the needs of caregivers are adequately and sufficiently addressed.